Little Hearts Are Affected by COVID19: Importance of the Myocardial Systolic Evaluation - Mamishi, Setareh; Zeinaloo, Aliakbar; Haji Esmaeil Memar, Elmira; Khodabandeh, Mahmoud; Mirzaaghayan, Mohammad Reza; Abdolsalehi, Mohammad Reza; Eshaghi, Hamid; Gorji, Mojtaba; Ghamari, Azin; Aghaei Moghadam, Ehsan (Frontiers in Pediatrics, 2021)
Background: Identifying the cardiac changes could help design measures to recover the cardiovascular system and lessen the mortality and morbidity rate. Accordingly, this cross-sectional study was performed to evaluate the echocardiography indices which are indicators of the cardiac alterations of the children with COVID19 infection. Methods: This study was performed as a cross-sectional study evaluating echocardiography indices in children infected with COVID19. Fifteen children, known cases of the COVID19, and 14 healthy children were enrolled. Evaluated parameters include left ventricle ejection fraction (LVEF), left ventricle end-diastolic diameter (LVED), mitral valve Sa (MV Sa), Tricuspid annular plane systolic excursion (TAPSE), and laboratory parameters. Results: The participants’ mean age and weight were 62.8(+48.0) months and 19.95 (+15.67) kg, respectively. None of the laboratory and echocardiography parameters differed between males and females, between patients with and without positive past medical history, between the patients with and without respiratory tract symptoms, and between patients with and without GI tract symptoms (P.0.05). Patients had significantly higher TAPSE (p=0.027), although MV Sa (p= 0.01) was significantly higher among healthy children. LV EF (p= 0.425) and LVED diameter (p=0.603) were not different significantly. None of the patients had pericardial effusion, pleural effusion, and cardiac tamponade. Conclusion: The heart can be involved during the disease course in children, even at the level of echocardiography indices. This could contribute to a worse prognosis, higher morbidity, and mortality rate, especially in patients with overt myocardial involvement. Nonclassic indicators, including LVEF, may not be conclusive for cardiac involvement in non-symptomatic patients.